Stakeholder Analysis in Tourism Development Bintan Regency During the Pandemic COVID-19 - Mahadiansar Mahadiansar; Andy Fefta Wijaya; Alfi Haris Wanto (Journal of Governance and Public Policy, 2021)
In improving the welfare of the people in border areas, the development of the tourism sector has an impact on long-term economic growth which has been the largest regional income source in Bintan Regency. The importance of interaction and stakeholder actors involved in tourism activities during the COVID-19 pandemic. The purpose of this study is to analyze the condition of stakeholder actors in tourism management in Bintan Regency. The research method used a qualitative approach with stakeholder analysis using NVivo 12 with data collection techniques in the form of interviews with stakeholders and using existing secondary data which was carried out in-depth analysis. The results showed that 3 components (who, when, and how) showed a significant correlation between stakeholders in tourism development in Bintan Regency, namely the local government which regulates the executive management as a facilitator. Then the involvement of community groups as active participation to support the development of travel bubble-based tourism in the border region of the country, then the involvement of the private sector who maintain and regulate health protocols in the spread of COVID-19. Furthermore, the alternative is to improve stakeholder relations in the future to make efforts to approach harmonious communication between stakeholders in the tourism sector in Bintan Regency.